Implications of the 2021 ESC cardiovascular risk classification among 283,000 European immigrants living in a low-risk region: a population-based analysis in Catalonia - Emili Vela; Montse Cleries; Usama Bilal; Maciej Banach; John W McEvoy; Martin Bødtker Mortensen; Michael Joseph Blaha; Khurram Nasir; Josep Comin-Colet; Josepa Mauri; Miguel Cainzos-Achirica (Archives of Medical Science, 2021)
Introduction The ESC recently classified European countries into 4 cardiovascular risk regions. However, whether Europeans from higher-risk countries living in lower-risk regions may benefit from intensive cardiovascular prevention efforts is unknown. We described the burden of risk factors and cardiovascular disease (CVD) among European-born immigrants living in Catalonia, a low-risk region.